The Influence of School Environment on Students' Social Behavior at SMA Negeri 1 Bone Bolango - NopriYanto Yahya; Meyko Panigoro; Mamang Kasim; Roy Hasiru; Sudriman Sudriman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aimed to examine the influence of the school environment on students' social behavior at SMA Negeri 1 Bone Bolango. This research employed a quantitative approach with a correlational design. The study involved 79 students as respondents. Data were collected using questionnaires and analyzed through descriptive statistics, simple linear regression, correlation analysis, coefficient of determination, and t-test using IBM SPSS Statistics 21. The findings showed that the school environment was categorized as very good, with a mean score of 4.21, while students' social behavior was categorized as good, with a mean score of 3.95. The regression analysis produced the equation Ŷ = 18.636 + 0.707X, indicating a positive relationship between the school environment and students' social behavior. The t-test results revealed that the school environment had a positive and significant effect on students' social behavior (t = 7.362, p < 0.05). In addition, the correlation coefficient was 0.643, indicating a strong relationship between the variables. The coefficient of determination (R²) was 0.413, meaning that 41.3% of the variation in students' social behavior was explained by the school environment, while 58.7% was influenced by other factors. Therefore, a positive school environment significantly contributes to the development of students' social behavior.